Spawn (1992): shadows ebook - McConville, Rory (Spawn (1992), 2024)
Get ready for an adrenaline-fueled ride through the world of SPAWN! Omega Spawn's lair is the site of an epic showdown, but when the Plague arrives, all bets are off. Meanwhile, Spawn and Medieval Spawn team up to escape the island, but trust is in short supply. And that's just the beginning! Spawn's Universe is more intense than ever with new shadow players and shocking revelations. Don't miss a moment of the action! Collects SPAWN #316-323